Effect of void ratio to the strength parameters of sedimentary rocks - Haryati, Awang; Song, Ki Il; Rini Asnida, Abdullah (Geological Society of Malaysia, 2019)
This paper is to study the influence of void ratio on the compressive and shear strength of sedimentary rocks at different degree of weathering. As void ratio is related to porosity therefore the present of void ratio should influence the mechanical properties of the porous sedimentary rocks such as sandstone and limestone. In order to determine the microstructures including pores and cracks of the samples, sandstone and limestone from different weathering grades were analyzed using photomicrograph analysis method. From the image of photomicrograph, the void ratio of the sample was calculated using image processing technique. The uniaxial compression and triaxial tests were carried out to determine the compressive and shear strength of the same samples by using GCTS Testing System. Results for void ratio, compressive and shear strength of the four different weathering grades of rocks were correlated to see the trend of relationships between the void ratio and the mechanical properties. In relation to weathering grades, the void ratio of the sedimentary rocks increases as the degree of weathering increases. The results also show that the void ratio and mechanical properties of sandstone are closely related. With the increase of void ratio, the compressive strength and shear strength decrease.